Using eHealth Tools for Patient-Healthcare Provider Communication in the Kingdom of Saudi Arabia: An Investigative Analysis - Basahih, Eman Obaid (Université d'Ottawa / University of Ottawa, 2020)
Background: Healthcare organizations worldwide are integrating eHealth tools such as mobile health applications into their systems to improve service delivery. Numerous relevant studies are currently underway, and many more are required to understand how these relatively new applications affect such factors as the cost of healthcare delivery, patient health/eHealth literacy, healthcare provider practice, workflow efficiency, and the patient–healthcare provider relationship. Objective: This study, which focused on eHealth tools [e.g., Sehaty application] used by the King Faisal Specialist Hospital and Research Center (KFSH&RC) in Riyadh, the Kingdom of Saudi Arabia (KSA), goes beyond most existing research by assessing the experiences of two user groups (patients and healthcare providers) and how their own needs are integrated through technology. At the heart of this research is how common ground is developed or constrained as communication is increasingly mediated through an electronic platform. Method: By employing a mixed-methods approach, quantitative data were collected from 107 patients through a cross-sectional survey, and qualitative data were gathered from 16 healthcare providers through an open-ended interview process at the KFSH&RC. We interpreted our data through the lens of common ground theory to understand how factors unique to each user group are mutually integrated into the common ground development cycle. Respective user groups and common ground factors were illustrated in our Patient–Healthcare Provider Factors and Functions for Communication (PHPFFC) model. Results: In this study, we present our results data in two chapters. First, we present our findings under the three research questions and five related assertions that guided our study. We show that eHealth tools affect patients’ health/eHealth literacy in a generally positive manner to the extent that healthcare providers perceive and anticipate efficiency gains in their workflows. Second, we present an adapted version of the PHPFFC model (i.e., PHPFFC V2.0) to reflect the empirical, context-specific findings of our study. Furthermore, we demonstrate that many constraints associated with mediated communication are overcome as common ground emerges in a stepwise pattern, through three stages: coordinative common ground; cooperative common ground; and collaborative common ground. We also illustrated common ground factors drawing from our three research questions and their links to the PHPFFC V2.0 model. Conclusion: This study examined patients and healthcare providers’ perspectives concerning technology acceptance as well as barriers to adopting eHealth tools in a healthcare setting. The findings from this empirical, context-specific study are intended to assist developers in understanding how user-group factors interact dynamically, and how such interactions may be facilitated through existing eHealth features and improved through the adaptation of new features.
Keywords: Electronic health systems; eHealth tools; eHealth literacy; Communication; Common ground; The Kingdom of Saudi Arabia